The effect of sand wind, temperature and exposure time on tri-layer polyethylene film used as greenhouse roof. (13th September 2016) - Djakhdane, K.; Dehbi, A.; Mourad, A-H. I.; Zaoui, A.; Picuno, P.
Abstract : This work aims at studying the degradable effect of artificial ageing on tri-layer stabilised low-density polyethylene (PE) films used as greenhouse cover in the North Africa environment. The film was supplied by Agrofilm company, Algeria. Colour additives and infra-red and ultraviolet stabilisers were used. Optical, thermal, surface and mechanical properties have been investigated for virgin sample and samples exposed to sand wind for different exposure periods (1, 2, 4 and 8 h) of artificial ageing at a temperature of 40°C simulating Saharan environment. The findings of this study show that the harsh environmental conditions of exposure to temperature and sand wind have significant degradable effects on the properties of the PE film. The transmission of the film and its mechanical properties have reduced significantly due to exposure to sand wind and temperature. The study revealed also that the degradation parameters measured are directly related to the criteria for evaluating the effectiveness of agricultural greenhouse.